Five new cave-dwelling species of Hemirrhagus Simon 1903 (Araneae, Theraphosidae, Theraphosinae), with notes on the generic distribution and novel morphological features - Mendoza, Jorge I.; Francke, Oscar F. (Zootaxa, 2018)
The suborder Mygalomorphae is generally poorly represented in the cave faunas of the world. The genus Hemirrhagus is endemic to Mexico and has 22 described species. It is the only one with epigean, troglophile and troglobitic species. Lack of urticating setae, loss of eye pigmentation and ocular reduction are interpreted as evolutionary reversals related to their troglobitic habits. From five troglobitic species in the genus, only the male of Hemirrhagus stygius is known. Five new troglobitic species are described with both sexes: Hemirrhagus akheronteus sp. nov., Hemirrhagus billsteelei sp. nov., Hemirrhaugus diablo sp. nov., Hemirrhagus kalebi sp. nov. and Hemirrhagus sprousei sp. nov. The female of Hemirrhagus chilango is described for the first time. Hemirrhagus akheronteus sp. nov. has a group of spinose setae on the opisthosoma; this setal modification was never reported in any other theraphosid spiders. Females of Hemirrhagus kalebi sp. nov. and Hemirrhagus sprousei sp. nov. lay fixed hammock egg sacs, which is an unusual behavior among species in Theraphosinae. Two stridulating setae previously reported only in epigean species are present on some of the new troglobites.